New non-destructive method for testing the strength of cement mortar material based on vibration frequency of steel bar: Theory and experiment - Shi, Hao; Song, Lei; Chen, Wenlong; Zhang, Houquan; Wang, Guozhu; Yuan, Guotao; Zhang, Wenliang; Chen, Guiwu; Wang, Yu; Lin, Gang (Elsevier, 2020)
Timely and accurately obtaining the strength of pouring material, e.g., concrete, cement mortar, is of great significance for engineering construction. In this paper, a non-destructive, economical and accurate strength detection method that suites for on-site using is proposed for the steel bar cement mortar material. The method based on the relationship between the vibration frequency of the steel bar and the properties of the mortar material, which is obtained by solving the Euler-Bernoulli beam problem. Both Particle Flow Code (PFC) software simulation (calibrated) and Split Hopkinson pressure Bar experiment on test samples of cement mortar and steel bar were performed to verify the theoretically obtained relationship. Studies on samples of various aggregate ratio further confirmed such correspondence. Results show that the dynamic stiffness of the cement mortar material dominates the calculation of the vibration frequency of steel bar, while the combined effect of the density, length, elastic modulus, inertia moment of the steel bar can be safely ignored. A single-valued mapping relation exists in between the dynamic stiffness coefficient and the Uniaxial Compressive Strength (UCS) of the cement mortar sample, i.e., increased dynamic stiffness coefficient with increasing UCS. Both experimental and predicted results showed a linear relationship between the vibration frequency of the steel bar and the strength of the mortar material. Fitted linear relations were proposed with coefficients depending on sample size and aggregate ratio and might serve as a good indicator for the strength of the mortar material. Further studies on the effect of internal defects of the mortar materials as well as on samples of more size and aggregate ratio are required to make the proposed method a practical tool
Keywords: Aggregate ratio; Theory and experiment; Strength detection; Vibration frequency of steel bar; Cement mortar material